Biomarker enzyme activities and ultrastructure of liver of the grass carp Ctenopharyngodon idella (Valenciennes, 1844) exposed to the organophosphate pesticide chlorpyrifos - Kaur, Mandeep; Jindal, Rajinder (Indian Journal of Fisheries, 2018)
The present investigation analysed the toxic effects of the organophosphate pesticide chlorpyrifos (CPF) on activities of biomarker enzymes viz., alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) and acid phosphatase (ACP) as well as ultrastructural alterations in hepatocytes of grass carp Ctenopharyngodon idella exposed to sublethal concentrations (1.44 and 2.41 Î¼g l-1) for 15, 30 and 60 days. The enzymes showed marked fluctuations postpesticide treatment. The altered enzymes activities indicated disturbance in the structure and integrity of cell organelles. Ultrastructural alterations such as formation of crescent shaped nucleus along with condensed chromatin, margination of heterochromatin, severe breakdown and fragmentation of endoplasmic reticulum, deformed mitochondria with loss of cristae were observed in the pesticide exposed fishes. The findings revealed exposure period and concentration dependent response in hepatocytes. Ultrastructural changes could be correlated to corresponding alterations in the activities of marker enzymes. At both the toxicant concentrations, altered activities of AST and ALT as markers of glycolysis and protein metabolism indicated disturbances to the cellular metabolism. The observed changes in the liver enzyme levels could be used as sensitive biomarkers for pesticides contamination in grass carp.